Ovarian cancer : disease, diagnosis, and treatment. (Elsevier, 2025)
By providing a comprehensive overview of current research findings, emerging therapies, and clinical practices, Ovarian Cancer: Disease, Diagnosis and Treatment is an invaluable resource.